Citizenship, activism and participation on the internet: brazilian experiences - Luvizotto, Caroline Kraus (2016)
A number of social and political actions have been strengthened and potentiated by internet support, with use of its network architecture to disseminate information, promote collective discussion and support activism. In order to discuss how internet tools can contribute to political and social participation in Brazil, were identified on two websites: Vote on the Web (Vote na Web), which is privately owned, and Participatory – Youth Participatory Surveillance (Participatório – Observatório Participativo da Juventude), which is the result of an initiative by the government through the National Youth Secretariat (Secretaria Nacional da Juventude - SNJ). From these examples, this study aims to analyze the use of the internet for the creation, organization and dissemination of social and political participation and online activism in Brazil. It is understood that the websites are limited and that online tools are not used to their full potential. However, considering a context of citizenship and online participation, it is possible to verify that the architecture of those websites encourages participation - even without civic engagement - and can be a step forward towards an enhanced civic practice.